Antimicrobial and anti-inflammatory properties of methyl palmitate and hexadecenoid acid in oral diseases: Sifat antimikroba dan antiinflamasi metil palmitat dan asam heksadekenoat dalam penyakit mulut - Asmawati Amin; Bahruddin Thalib; Adilah Zahirah Fitri Djerman; Dian Mentari Putri (Makassar Dental Journal PDGI Makassar, 2026)
Oral diseases such as periodontitis and mucositis involve microbial biofilms and immune system disorders. Marine-derived lipid compounds such as methyl palmitate (MP) and hexadecenoic acid (AHD) exhibit promising antimicrobial and anti-inflammatory properties. This review compiles current preclinical and clinical evidence on their mechanisms and therapeutic potential in oral diseases. A systematic search (2015–2025) through PubMed, Scopus, and Google Scholar was conducted using the PICOS framework, covering in vitro, animal, and clinical studies. Narrative synthesis was applied due to data variability. MP appears to reduce TNF-? and IL-1? by inhibiting NF-?B in macrophages and increasing IL-10. AHD decreases IL-6, IL-18, and MCP-1, promotes M2 polarisation, and disrupts biofilm. Both compounds are derived from marine sources such as fish oil and microalgae. It is concluded that MP and AHD have potential as adjunctive therapies for oral inflammation, although further clinical validation is essential.